Desarrollo de paneles prefabricados de hormigón con fibras de polipropileno, aplicando fibras de cáscara de semillas de girasol - Cornejo Núñez, Juliana Yamilet (2025)
The construction industry is currently facing significant challenges regarding sustainability and the environmental impact of various materials. Ecuador is a country that traditionally relies on construction materials that contribute to high levels of pollution due to the excessive consumption of non renewable resources and the generation of waste throughout the different construction phases. As a result, the sustainable materials market lacks momentum, and the adoption of sustainable practices faces challenges such as limited regulatory incentives. This study proposes the development of a prototype prefabricated concrete panel reinforced with different types of polypropylene fibers and sunflower seed shells for non-structural uses, aiming to assess its environmental and structural feasibility. An extensive literature review was conducted, including both national and international sources, to understand the use of natural fibers in concrete across Latin America, Asia, and Europe. The results indicate that incorporating plant-based fibers improves the mechanical properties of concrete, including its durability, and contributes to reducing the carbon footprint, thus promoting the field of sustainable construction..........